2007
DOI: 10.1038/ismej.2007.60
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cattle husbandry on abundance and activity of methanogenic archaea in upland soils

Abstract: In the present study, we tested the hypothesis that animal treading associated with a high input of organic matter would favour methanogenesis in soils used as overwintering pasture. Hence, methane emissions and methanogen populations were examined at sections with different degree of cattle impact in a Farm in South Bohemia, Czech Republic. In spring, methane emission positively corresponded to the gradient of animal impact. Applying phospholipid etherlipid analysis, the highest archaeal biomass was found in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
54
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 40 publications
6
54
0
1
Order By: Relevance
“…Grazing induced increases in the number of copies of the mcrA gene and soil CH 4 emissions (Radl et al 2007). In our study, the relative abundance of the CH 4 -producing mcrA gene increased at the 3200-m site, but CH 4 -oxidizing genes decreased at both sites (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Grazing induced increases in the number of copies of the mcrA gene and soil CH 4 emissions (Radl et al 2007). In our study, the relative abundance of the CH 4 -producing mcrA gene increased at the 3200-m site, but CH 4 -oxidizing genes decreased at both sites (see Supplementary Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, grassland recovery after grazing is a common land-use management strategy in many places around the world. Grassland recovery has been shown to fully restore plant growth and certain eco-processes (e.g., CH 4 emissions) if grazed at moderate intensity, but grazing at high intensity leads to soil deterioration (Cao et al 2004;Pappas and Koukoura 2013;Radl et al 2007). Therefore, it is necessary to examine functional potentials of microbial communities in post-grazing grassland soils.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, N 2 O effluxes varied linearly with fungi biomass in freshwater sediments (Takaya 2009;Seo & DeLaune 2010;Mouton et al 2012). However, although it has been reported that microbial biomass influenced GHG emissions in terrestrial soils (Radl et al 2007;Burke et al 2012;Narvaez et al 2013), few studies have focused on investigating the effects of microbial biomass on GHG emissions in lake sediments.…”
Section: Introductionmentioning
confidence: 99%